Harmony of freedom / Arifah Fasha Rosmani - Rosmani, Arifah Fasha (Unit Penerbitan e-Buletin JSKM, 2024)
In the heart of Southeast Asia's embrace, A nation awakens with dignity and grace. Malaysia, a land of diverse hues, Where unity blooms, a shared muse.